Congenital Lumbar Hernia Associated with Duodenal Atresia and Lumbo-costo-vertebral Syndrome - Kamal Nain Rattan; Arushi Agarwa; Ankur Dhiman; Ananta Rattan (JCDR Research and Publications Pvt. Ltd., 2016)
Congenital lumbar hernia is associated with a multitude of congenital anomalies involving various other organ systems of the body. These involve the ribs, spine, muscles, kidneys, and spinal meninges. We are reporting a case of one day old male child with congenital lumbar hernia associated with duodenal atresia and lumbo-costo-vertebral syndrome. We failed to find this association in literature. This prompted us to report this rare case.